Memórias das aritméticas da Emília: o ensino de aritmética entre 1920 e 1940 - Oliveira, Adriel Gonçalves [UNESP] (2015)
This research claims to investigate how practices of arithmetic teaching manifest explicitly in the fictional work Aritmética da Emília, by the brazilian writer Monteiro Lobato (1882 - 1948). Besides, it dialogues to tracks of others cultural practices the mentioned book can point to, based on the historical context of mathematical teaching between 1920 and 1940. Our analysis follows to intertextuality methods between a several documents from this period, such as A Aritmética da Emília (1935, 1° edition, 1939; 2° edition; 1942, 3° edition; 1944, 4° edition), Aritmética da Emília (1947); others works made by Lobato; arithmetics books written at that time; laws about teaching; letters between Lobato and Anísio Teixeira; letter between Lobato and Julio Cesar de Mello e Souza; magazines on teaching; texts on decades 1920 and 1940 education; youth literature books. We have as a reference Chartier, Burke and Ginzburg. We concluded that Aritmética da Emília shows all philosophical and pedagogical contradiction of those years, confronting the didactic tradition of conservative education with the renewal movement of the New School, swinging the innovative nature of its pedagogical proposal and falling in pratices professorial of those times